MAIN TRENDS OF DEVELOPING MEDICAL TOURISM IN GEORGIA - Otar Gerzmava; Ana Tegetashvili (European Scientific Journal, ESJ, 2016)
Medical tourism is becoming increasingly popular. This phenomenon is driven by marketplace forces and occurs outside of the view and control of the organized healthcare system. Medical tourism presents important concerns and challenges as well as potential opportunities. In the recent past, a trend known as medical tourism has emerged wherein citizens of highly developed countries choose to medical care offered in their own communities and travel to less developed areas of the world to receive a wide variety of medical services. This trend will have increasing impact on the healthcare landscape in industrialized and developing countries around the world. Medical tourism in Georgia is developed unequally. Along with Turkey the recognised leader of Medical tourism, who remain the world’s top destinations for medical tourists and foreign investors, in Georgia this direction only starts to develop. At the same time in the country there are all conditions for development of this branch: • Internationally recognized quality standards. • Extensive diagnostic and therapeutic resources. • Modern healthcare facilities - the infrastructure and the healthcare facilities available in South Caucasian countries conform to the world standards. • Highly efficient medical staff - one can find a large number of medical professionals • The cost of getting the treatment can be done at less than half the cost and the patient gets the best possible treatment available.